Effect of sand versus grass training surfaces during an 8-week pre-season conditioning programme in team sport athletes - Binnie, M. J.; Dawson, B.; Arnot, M. A.; Pinnington, H.; Landers, G.; Peeling, P. (Journal of Sports Sciences, 2014)
This study compared the use of sand and grass training surfaces throughout an 8-week conditioning programme in well-trained female team sport athletes (n = 24). Performance testing was conducted pre- and post-training and included measures of leg strength and balance, vertical jump, agility, 20 m speed, repeat speed (8 × 20 m every 20 s), as well as running economy and maximal oxygen consumption (VO2max). Heart rate (HR), training load (rating of perceived exertion (RPE) × duration), movement patterns and perceptual measures were monitored throughout each training session. Participants completed 2 × 1 h conditioning sessions per week on sand (SAND) or grass (GRASS) surfaces, incorporating interval training, sprint and agility drills, and small-sided games. Results showed a significantly higher (P < 0.05) HR and training load in the SAND versus GRASS group throughout each week of training, plus some moderate effect sizes to suggest lower perceptual ratings of soreness and fatigue on SAND. Significantly greater (P < 0.05) improvements in VO2max were measured for SAND compared to GRASS. These results suggest that substituting sand for grass training surfaces throughout an 8-week conditioning programme can significantly increase the relative exercise intensity and training load, subsequently leading to superior improvements in aerobic fitness.